Post-Merger Share Price Performance Analysis: A Case Study of UBA Group Plc. - Ogundipe, Oyekunbi (2009)
Abstract. Mergers have been taught of as a form of corporate development and most organisations use it as a route to achieving economies of scale and scope amongst others. This piece of work sheds light on a government induced merger that took place in the Nigerian banking sector and tries to examine how the share price has performed post merger. We conclude that a country initiated merger is not the ultimate form of corporate development but rather a market induced merger would have been more appropriate as the performance of the stock market and share price has taken a downward swing post consolidation. Keywords: Merger, Share Price, Emerging Market, Banking Sector. 2